Foreign Worker Governance in Indonesia: Institutional Challenges and Strategic Reform Pathways - Zhu Xi; Stephanus Remond Waworuntu (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
Indonesia’s accelerating economic transformation has increased reliance on foreign workers, yet its governance system continues to face persistent institutional and implementation challenges. This study systematically analyzes the evolution, structural dilemmas, and strategic optimization pathways of Indonesia’s foreign worker management policy. Using a structured qualitative review grounded in Institutional Theory and Stakeholder Theory, the research synthesizes regulatory frameworks, government statistics, policy reports, and relevant academic literature. Findings reveal a sustained disconnect between regulatory intent and operational practice: although official work permit processing targets 12 working days, actual completion frequently extends to 30–60 days. A discrepancy of approximately 86,000 workers between registered and estimated actual figures indicates significant irregular employment. Rights protection mechanisms remain uneven, with documented wage arrears and occupational vulnerabilities in labor-intensive sectors. These issues reflect misalignment across regulative, normative, and cultural-cognitive institutional pillars, compounded by fragmented stakeholder interests. The study proposes an integrated governance model that combines digital coordination, strengthened enforcement, and structured socio-cultural integration initiatives. Such reforms align with SDG 8 (Decent Work) and SDG 10 (Reduced Inequalities), offering a strategic pathway toward more coherent, equitable, and sustainable labor migration governance